Stepfamilies in Europe, 1400-1800
1 online resource (xviii, 288 pages)
Keywords: "Stepfamilies were as common in the European past as they are today. Stepfamilies in Europe, 1400-1800 is the first in-depth study to chart four centuries of continuity and change for these complex families created by the death of a parent and the remarriage of the survivor. With geographic coverage from the Mediterranean to Scandinavia and from the Atlantic coast to Central Europe, this collection of essays from leading scholars compares how religious affiliation, laws and cultural attitudes shaped stepfamily realities. Exploring stepfamilies across society from artisans to princely rulers, this book considers the impact of remarriage on the bonds between parents and their children, stepparents and stepchildren, while offering insights into the relationships between full siblings, half siblings and stepsiblings. The contributors investigate a variety of primary sources from songs to letters and memoirs, printed Protestant funeral works, Catholic dispensation requests, kinship puzzles, legitimation petitions, and documents drawn up by notaries, to understand the experiences and life cycle of a family and its members--whether growing up as a stepchild or forming a stepfamily through marital choice as an adult.Featuring an array of visual evidence, and drawing on topics such as widowhood, remarriage, and the guardianship of children, Stepfamilies in Europe will be essential reading for scholars and students of the history of the family."--Provided by publisher.